The moderating effect of brand loyalty on service quality and customer satisfaction in the telecommunications industry in northwest Nigeria - Ibrahim, Bashir Musa; Abubakar, Ahmadu (Journal of Accounting, Business and Finance Research, 2023)
This study investigates the moderating effect of brand loyalty on service quality and customer satisfaction in the telecommunications industry in Northwest Nigeria. A cross-sectional descriptive survey design was utilized, which permits the collection of data from respondents at a certain point in time. The convenience sampling method was used, and structured questionnaires were administered to the customers of Airtel Nigeria telecommunications company using a service performance (SERVPERF) model. Out of the 768 questionnaires administered, 390 valid responses were analyzed, and the hypotheses were tested with the aid of SmartPLS 4. The results for the direct relationships indicate that reliability, assurance, responsiveness, and tangibility were significantly and positively related with customer satisfaction, while empathy had no significant effect on customer satisfaction. For the indirect relationships, brand loyalty was not found to moderate the relationships between the five SERVPERF dimensions and customer satisfaction. The study concludes that regardless of brand loyalty, service quality remains the only driving force of customer satisfaction in the Nigerian telecommunications industry. It is therefore recommended that Airtel should find ways to transcend their competitors and ensure the continued loyalty of their subscribers, especially by tailoring services to customers’ needs. It is also recommended that the company should ensure a pleasant and seamless experience for their subscribers during calls or when accessing the internet. The Nigerian Communications Commission (NCC) should continue to monitor the quality of the services provided by telecommunications companies and sanction those that provide sub-standard services.